Growth Mindset Based Career Counseling to Enhance University Students' Resilience in Responding to the Dynamics of the Society 5.0 Labor Market - Putri NurulAzizah; Amelia GitaMaharani; Brilian GalangIrzaqi; Jumhuriyatus Sadiyah; Dwi SeptiRahayu; Rahmi Anekasari (The Future of Education Journal, 2026)
The advancement of technology in the Society 5.0 era has brought significant changes across various aspects of life, including education and the labor market. As future professionals, university students are expected not only to possess strong academic competencies but also to demonstrate critical thinking, adaptability, creativity, communication, collaboration, and psychological resilience in responding to rapid changes. These demands often give rise to psychological challenges, such as career anxiety, uncertainty about employment opportunities, and low self-confidence. Consequently, effective strategies are needed to help students prepare for these challenges. This article aims to examine the role of growth mindset-based career counseling as a strategy for enhancing university students' resilience in navigating the dynamic labor market of the Society 5.0 era. The study employed a library research approach by reviewing relevant scholarly journals, books, and other academic literature on growth mindset, career counseling, career adaptability, and student resilience. The findings indicate that the implementation of a growth mindset fosters more positive attitudes toward challenges, enhances adaptability, strengthens career maturity, and promotes resilience in coping with failure and the evolving demands of the workplace. The effectiveness of growth mindset-based career counseling is influenced by institutional support, counselors' professional competence, and students' willingness to engage in continuous learning and self-development. Conversely, low resilience, limited career maturity, and inadequate social support may hinder its successful implementation. Therefore, growth mindset-based career counseling represents an effective strategy for preparing university graduates to become resilient, adaptable, competitive, and well-equipped to meet the challenges of the Society 5.0 workforce.